2020
DOI: 10.1186/s40814-020-00645-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of a Dalcroze eurhythmics and a simple home exercise program among older adults with mild cognitive impairment (MCI) or mild dementia: the MOVE for your MIND pilot trial

Abstract: Background: Falls represent a major health problem for older adults with cognitive impairment, and the effects of exercise for fall reduction are understudied in this population. This pilot randomized controlled trial evaluated the feasibility, safety, and exploratory effectiveness of a Dalcroze eurhythmics program and a home exercise program designed for fall prevention in older adults with mild cognitive impairment (MCI) or early dementia. Methods: For this three-arm, single-blind, 12-month randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 33 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The mean age of the participants in the reviewed studies was 61.91 years. Concerning sex, 27 included men and women in their sample [29‒31, 37, 40‒62], four had a sample composed only of men [38, 39, 63, 64], two composed only of women [65, 66], and one did not specify the gender in its sample [67]. Regarding the types of exercises targeted at the intervention groups, the combined rehabilitation training programs involved: dual-task gait training [45, 58, 62], aerobic and cognitive training [29, 40, 54, 59, 60, 66], aerobic activity and strength activity [44, 46], Tai Chi [41, 56], aerobic and endurance training [30, 50, 63, 64].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean age of the participants in the reviewed studies was 61.91 years. Concerning sex, 27 included men and women in their sample [29‒31, 37, 40‒62], four had a sample composed only of men [38, 39, 63, 64], two composed only of women [65, 66], and one did not specify the gender in its sample [67]. Regarding the types of exercises targeted at the intervention groups, the combined rehabilitation training programs involved: dual-task gait training [45, 58, 62], aerobic and cognitive training [29, 40, 54, 59, 60, 66], aerobic activity and strength activity [44, 46], Tai Chi [41, 56], aerobic and endurance training [30, 50, 63, 64].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the type of rehabilitation training program, of the 23 studies that used combined rehabilitation training programs, 20 recorded cognitive improvements after completing the recommended exercise sessions [29, 30, 38, 40, 41, 44, 45, 47, 50‒52, 54, 56, 58‒63, 66], while three did not record cognitive improvements [46, 64, 65]. Concerning the 11 studies that followed an isolated rehabilitation training recovery program, seven reported cognitive improvements [31, 37, 42, 43, 53, 55, 67], and four reported no cognitive improvements [39, 48, 49, 57] (online suppl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations